Role of Myostatin in oxidative stress in skeletal muscle - Sandhya Sriram (2013)
Skeletal muscle is a metabolically active tissue that is highly susceptible to wasting via oxidative stress. Oxidative stress, caused by excessive generation of reactive oxygen species, leads to skeletal muscle wasting during various diseases including cancer, diabetes and sarcopenia via various signaling molecules including TNF-α, NADPH oxidase, NF-κB, MAPKs and IL-6. However, the exact mechanism involved in oxidative stress-induced muscle wasting is not known. In the recent years, Myostatin, a member of the TGF-β superfamily and a negative regulator of skeletal muscle growth and development, has been identified as a potent inducer of muscle wasting. Here, in this thesis using various in vitro and in vivo approaches, I present that Myostatin acts as a pro-oxidant leading to skeletal muscle wasting. Firstly, this thesis demonstrates that Myostatin induces reactive oxygen species in skeletal muscle cells through TNF-α signaling via NF-κB and NADPH oxidase. In addition, Myostatin and TNF-α are components of a ‘feed forward’ loop in which Myostatin triggers reactive oxygen species generation via TNF-α and the elevated TNF-α in turn stimulates Myostatin expression. The sustained reactive oxygen species production leads to increased proteasomal-mediated degradation of proteins resulting in skeletal muscle wasting. Genetic inactivation of Myostatin in young and aged mice increased the basal Antioxidant Enzyme levels and lowered NF-κB levels, thus offering resistance to oxidative stress. Since aged Myostatin-/- mice also have lower levels of NF-κB in the muscle, I propose that Myostatin would be a good candidate to target during sarcopenia. To further understand Myostatin signaling of NF-κB and reactive oxygen species, Smad3-/- mice was used as a model since Smads are crucial downstream targets of Myostatin. Recently, our laboratory showed that Smad3-/- mice have pronounced muscle atrophy which was attributed to the increased Myostatin levels in these mice. Hence, I investigated if Smad3-/- mice have increased reactive oxygen species and our results indicated that indeed these mice have elevated oxidative stress in skeletal muscle. Inactivation of Myostatin in the absence of Smad3 partially alleviates the oxidative stress. Even though, increased Myostatin in Smad3-/- mice induced excessive reactive oxygen species, NF-κB signaling was not activated in these mice. This led us to propose that Smad3 is necessary for Myostatin-induced oxidative stress via NF-κB. Reactive oxygen species generation by Myostatin in mice lacking Smad3 was by activation of complex signaling pathways that include p38, ERK MAPK and crosstalk with the JAKs and STATs. Activation of these signaling cascades increased TNF-α, NADPH oxidase and Xanthine oxidase levels resulting in exaggerated reactive oxygen species production in Smad3-/- muscles. The excessive reactive oxygen species generated led to increased binding of CHOP transcription factor to MuRF1 promoter resulting in enhanced muscle atrophy. To advance our understanding of the effect of Myostatin-induced reactive oxygen species in skeletal muscle, a type 1 diabetes mouse model via Streptozotocin administration was used. During type 1 diabetes, there is pronounced muscle wasting due to excessive oxidative stress also leading to DNA damage. In the recent years, Myostatin has been shown to be up-regulated during Streptozotocin-induced type 1 diabetes in rodents. Since I showed that Myostatin can cause oxidative stress in muscle cells leading to protein degradation, I wanted to investigate if Myostatin can induce DNA damage also. Using an integrative approach from cell cultures to mice, I show that Myostatin can induce DNA damage via p63/REDD1 pathway in skeletal muscle. Moreover, inhibition/inactivation of Myostatin partially rescued DNA damage by regulating DNA damage/repair mechanisms. Additionally, our results also demonstrate that hypoinsulinemia during type 1 diabetes increased Myostatin levels via FoxA2. In conclusion, the data presented in this thesis indicates that Myostatin is a pro-oxidant that can induce oxidative stress leading to skeletal muscle wasting, by not only increasing protein degradation but by also causing DNA damage.